A New Species of Oochoristica (Cestoda, Linstowiidae) from the Arabian Toad-Headed Agama, Phrynocephalus arabicus (Sauria, Agamidae), from the United Arab Emirates - Schuster, R.K. (Вестник зоологии, 2012)
Eight complete strobilae of Oochoristica phrynocephali Schuster, sp. n. were recovered from small intestines of 4 out of 13 Arabian toad-headed agamas, Phrynocephalus arabicus from Dubai emirate, United Arab Emirates. O. phrynocephali belongs to a group of Oochoristica species possessing circular suckers and fewer than 25 testes in a single cluster. It can be distinguished from O. sobolevi, O. elongata, O. parvogenitalis, O. feliui, O. jonnesi, O. macallisteri, O. lygosomatis, O. junkea and O. novaezealandae by smaller scolices and lesser diameter of suckers. Шесть полных стробил Oochoristica phrynocephali Schuster, sp. n. были обнаружены в кишечнике 4 из 13 исследованных арабских круглоголовок Phrynocephalus arabicus из эмирата Дубаи, Объединённые Арабские Эмираты. O. phrynocephali относится к группе видов Oochoristica с круглыми присосками и числом семенников меньшим 25 в каждом кластере. Вид отличается от O. sobolevi, O. elongata, O. parvogenitalis, O. feliui, O. jonnesi, O. macallisteri, O. lygosomatis, O. junkea и O. novaezealandae меньшим сколексом и меньшим диаметром присосок.